KONTRIBUSI PARTISIPASI KOMITE TERHADAP MUTU LAYANAN PENDIDIKAN DI MAN SEKABUPATEN TANAH DATAR - Sudirman Sudirman (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Contribution of Participation Committee on the Quality of Services Education in MAN seKabupaten Tanah Datar. The purpose of this research is to know whether the committee participation has contribution to educational service quality in MAN at Tanah Datar Regency. The population of this study is all of teachers of Islamic Senior High School (MAN) that consist of 145 teachers, and sample of this research is 53 teachers by using proportional stratified random sampling. The data are got by using questionairs, those are analized by using Statistical Package for Social Science (SPSS).The findings of the research is that the committee participation has contribution to the quality of educational services. The number of contribution is 0,206. It means that if the participation of the committee is increased, the quality of educational services is good, and vice versa. From the research, it can be concluded that the committee has to improve its participation in schools’ activities in order to improve the quality of educational services.Kata Kunci: Partisipasi komite, mutu layanan pendidikan